2012
DOI: 10.5489/cuaj.10122
|View full text |Cite
|
Sign up to set email alerts
|

Variables influencing the likelihood of cardiac dysrhythmias during extracorporeal shock wave lithotripsy

Abstract: Introduction: Extracorporeal shock wave lithotripsy (ESWL) is a safe and effective treatment of upper urinary tract calculi. While serious side effects are rare, transient cardiac dysrhythmias (CD) may be associated with ESWL. The exact etiology of these events, which are often unpredictable, is poorly understood. Awareness of CD during ESWL and identification of risk factors for developing them could help clinicians predict and manage them safely and effectively. The current study examines selected variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Arrhythmias were commonly related to the right-sided procedures ( p < 0.05) but were not related to age, sex, pre-existing heart disease, stone size, location, ureteral stent presence, anesthesia mode, and total shock number. Thomas et al reported similar outcomes in 342 patients and found that arrhythmias were common in younger patients and right-sided procedures ( 5 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Arrhythmias were commonly related to the right-sided procedures ( p < 0.05) but were not related to age, sex, pre-existing heart disease, stone size, location, ureteral stent presence, anesthesia mode, and total shock number. Thomas et al reported similar outcomes in 342 patients and found that arrhythmias were common in younger patients and right-sided procedures ( 5 ).…”
Section: Discussionmentioning
confidence: 91%
“…The ECG lead is patched; synchronization is started when the cardiac cycle is recognized; and then, shockwave release is avoided during the relative refractory period. The incidence rate of arrhythmias under synchronized ESWL is 11%−59%, whereas, under unsynchronized ESWL, it is 60%−80%; however, arrhythmias during synchronized ESWL are mostly benign and do not require intervention ( 5 ). Unifocal PVCs were mostly recorded ( 4 , 6 ); multiple PVCs and supraventricular tachycardia have also been reported.…”
Section: Discussionmentioning
confidence: 99%